Legal Provisions and Administration of Land Disputes in Kiteto District, ca. 1970s – 2000s: The Missing Linkage - Marmo, Juma (Zamani: A Journal of African Historical Studies, 2024)
There have been a series of legal interventions on land use in the post-colonial Tanzania to create a good land administration and management in order to end land use conflicts. Scholarship on the legal aspect of land use indicates that legal interventions did not provide lasting solutions to land use conflicts because of their structural and systemic arrangements. In addition, existing scholarship has little focus on the linkage between law enforcement machinery, the peoples’ level of understanding on land laws, and the occurrence of land use conflicts. This paper discusses the violation of laws by peasants, pastoralists, and government officials at different levels and its connection to the outbreak of land use conflicts between peasants and pastoralists in the Kiteto district. Using archival and oral sources, I argue that land use conflicts between peasants and pastoralists in Kiteto are the outcome of violation of land laws by the major stakeholders at different levels, inaccessibility to the legal services, poor understanding of the land laws and lack of coordination among the respective legal organs. This paper contributes to the historiography of legal interventions in conflict resolution by bringing forward the position of major stakeholders in implementing land laws.